Methylation analysis as a diagnostic tool for sweat gland tumours classification with emphasis on the distinction between digital papillary adenocarcinoma and mimickers - Sohier, Pierre; Macagno, Nicolas; Tallet, Anne; Mousset, Coralie; Battistella, Maxime; Calonje, Eduardo; Deimling, Andreas von; Kervarrec, Thibault (Histopathology, 2025)
AimsDigital papillary adenocarcinoma (DPA) is a rare sweat gland carcinoma arising on acral sites. The main differential diagnosis included tubular adenoma, hidradenoma, poroid hidradenoma, and mixed tumours, distinction between DPA and these mimickers being crucial for therapeutic management. Recently, HPV42 was identified as the main oncogenic driver of most DPA. Controversially, a few sweat gland tumour cases diagnosed as "DPA" but lacking the HPV42 genome and harbouring instead a BRAFV600E mutation, a genetic hallmark of tubular adenomas, have been recently described. Methylation analysis is a powerful tool for tumour classification systems. In this context, the aim of the present study is to evaluate the accuracy of methylation analysis for sweat gland tumour classification with special emphasis on the distinction between DPA and mimickers.Methods and resultsTwelve DPA, 11 tubular adenomas, 12 hidradenomas, 8 apocrine and 6 eccrine mixed tumours, 7 poromas and 6 adnexal sweat gland carcinoma not otherwise specified (NOS) were submitted for DNA methylation profiling. The results of this analysis show that most of these tumour types formed their own unique cluster, setting them apart from the others. In particular, DPA cases clustered together and were distinct from other tumour entities including tubular adenomas.ConclusionsOur data support the distinction between DPA and tubular adenomas as two unique entities and further confirm DNA methylation profiling as a relevant tool for tumour classification.
Veröffentlicht: 10 June 2025
Gesehen am 03.11.2025